2022
DOI: 10.4103/eus-d-21-00151
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography

Abstract: Physicians have used palpation as a diagnostic examination to understand the elastic properties of pathology for a long time since they realized that tissue stiffness is closely related to its biological characteristics. US elastography provided new diagnostic information about elasticity comparing with the morphological feathers of traditional US, and thus expanded the scope of the application in clinic. US elastography is now widely used in the field of diagnosis and differential diagnosis of abnormality, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 153 publications
0
27
0
Order By: Relevance
“…Two-dimensional SWE relies on the quantification of the SWS to estimate tissue elasticity. Unlike strain imaging, where physical tissue displacement is quantified, 2D-SWE uses a dynamic stress to create measurable parallel or perpendicular shear waves 28–30 . There are three 2D-SWE techniques in use: (1) 1-dimensional transient elastography, (2) point shear wave elastography (pSWE), and (3) 2D-SWE.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional SWE relies on the quantification of the SWS to estimate tissue elasticity. Unlike strain imaging, where physical tissue displacement is quantified, 2D-SWE uses a dynamic stress to create measurable parallel or perpendicular shear waves 28–30 . There are three 2D-SWE techniques in use: (1) 1-dimensional transient elastography, (2) point shear wave elastography (pSWE), and (3) 2D-SWE.…”
Section: Discussionmentioning
confidence: 99%
“…Deformation is induced by manually applying micropressure with the ultrasound probe or by means of ultrasound pulses of appropriate intensity [ 49 , 51 , 52 , 53 , 54 , 55 ]. In the second excitation method, the ultrasound transducer remains stationary, while tissue displacement is caused by internal physiological movements (e.g., cardiac and arterial pulsations and respiratory motion).…”
Section: Relevant Sectionsmentioning
confidence: 99%
“…In both cases, the ultrasound images before and after the compression are then compared, and the equipment generates a color map that expresses the relative elasticity of the different tissue components, finally showing a specific “deformation index”. Usually, blue is used to represent low strain (i.e., stiff tissue), and red is used to represent high strain (i.e., soft tissue), although the specific color may differ based on the manufacturer of the ultrasound device [ 40 , 52 , 54 ]. SE assesses the relative stiffness of tissues within the elastographic ROI superimposed on a B-mode ultrasound image, requiring precise alignment of the ROI with the Peyronie’s plaque.…”
Section: Relevant Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that acoustic radiation force impulse (ARFI) is more effective than TE in patients with ascites and obesity, and also has a lower failure rate [ 7 ]. ARFI has a sensitivity and specificity of 92% and 86%, respectively, for diagnosing cirrhosis [ 8 ]. ARFI has been successfully applied to liver diseases such as chronic hepatitis B and C, and can be recommended as a reliable tool for monitoring liver fibrosis [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%